Activity-Based Concept Towards Office Building in Jakarta - Melyna Melyna; Naniek Widayati Priyomarsono; Fermanto Lianto (Petra Christian University, 2024)
Post-COVID-19 pandemic work activities faced a readjustment, but work activities are now more flexible regarding place and time. Therefore, it is necessary to reconsider current work activities, which are now based on the workers’ activities. Office buildings are a main physical factor in comfort and worker productivity. With an activity-based concept based on the worker’s activities, office building configuration is based on the needs of each worker at a time and consists of several types of workspaces. The research uses the multiple case study method to reassess the role of office buildings in current work activities. The design method used is Bernard Tschumi’s programming theory. The activity-based concept is structured based on elements of the physical work environment implemented in several types of work areas according to needs, with the most significant space configuration being the facility area.